2001
DOI: 10.1046/j.1523-1747.2001.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Variegate Porphyria: 20 y Follow-Up and Characterization of Molecular Defect

Abstract: The long-term follow-up of a homozygous variegate porphyria patient revealed severe photosensitivity accompanied by mild sensory neuropathy and IgA nephropathy. A 35T to C transition in exon 2 (I12T) and a 767C to G transversion in exon 7 (P256R) of the protoporphyrinogen oxidase gene were identified from both alleles of the patient's cDNA and genomic DNA samples. Both prokaryotic and eukaryotic expression studies showed that the first mutation in the evolutionary conserved region resulted in a decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…Six of the Finnish VP mutations are family-specific and found so far only in Finland, whereas the major mutation (R152C), which was identified in 11 (52%) of the 21 Finnish VP families, has also been reported in France and in the USA. 29,31 As previously reported, 40,41 six of the mutations have been expressed in prokaryotic and eukaryotic cell systems. The PPOX activities of the mutated polypeptides were markedly reduced (45% , Table 1) confirming that the mutations are responsible for the disease.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Six of the Finnish VP mutations are family-specific and found so far only in Finland, whereas the major mutation (R152C), which was identified in 11 (52%) of the 21 Finnish VP families, has also been reported in France and in the USA. 29,31 As previously reported, 40,41 six of the mutations have been expressed in prokaryotic and eukaryotic cell systems. The PPOX activities of the mutated polypeptides were markedly reduced (45% , Table 1) confirming that the mutations are responsible for the disease.…”
Section: Introductionmentioning
confidence: 57%
“…The family became aware of VP mainly due to a homozygous patient with a severe phenotype. 40 The occurrence of photosensitivity was significantly lower in the I12T group compared to the R152C group (P=0.001), whereas no significant differences between the R152C and 338G?C groups could be observed.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Seven mutations selected for this study were previously identified from Finnish VP patients and expressed in Escherichia coli and COS-1 cells (Table I) (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Most patients are heterozygous, exhibiting approximately 50% reduced PPOX activity (Brenner and Bloomer 1980;Deybach et al 1981). However, since the first description of a homozygous VP case in 1984 (Korda et al 1984), several homozygous and compound heterozygous cases have been reported (Hift et al 1993;Kauppinen et al 2001;Poblete-Gutiérrez et al 2006).…”
Section: Introductionmentioning
confidence: 99%